Carbide superhigh-temperature ceramic nanoparticle-graphene composite material as well as rapid preparation method and application thereof
Through Joule heating method, the reduction of graphene oxide and the rapid and uniform synthesis of carbide ultra-high temperature ceramic nanoparticles on graphene are achieved under short-term, rapid and uniform synthesis of carbide ultra-high temperature ceramic nanoparticles on graphene, solving the problems of composite materials not increasing but decreasing, complex processes and high energy consumption in the prior art, and achieving efficient and environmentally friendly composite materials preparation.
Patent Information
- Application Number
- CN202411844078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-15
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to achieve uniform mixing of carbide ultra-high temperature ceramic nanoparticles and graphene, resulting in the performance of composite materials not increasing but decreasing. The traditional synthesis method has complex processes, long cycles, high energy consumption and large environmental pollution.
The Joule heating method is used to synchronize the reduction of graphene oxide and the rapid and uniform synthesis of carbide ultra-high temperature ceramic nanoparticles on graphene through short-term rapid and high-temperature thermal shock.
The uniform distribution of carbide ultra-high temperature ceramic nanoparticles and graphene is achieved, the thermal conductivity, electrical conductivity and mechanical properties of composite materials are improved, the preparation process is simplified, the preparation cycle is shortened, energy is saved, and the environment is protected.
Smart Images

Figure CN119661226A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ultra-high temperature carbide ceramic nanomaterials, and relates to a carbide ultra-high temperature ceramic nanoparticle-graphene composite material and a rapid preparation method and application thereof, and specifically relates to a method for preparing a carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-time rapid high-temperature thermal shock. Background Art
[0002] Ultra-high temperature ceramics include carbide ceramics, boride ceramics, nitride ceramics, etc., which have the characteristics of high strength, high hardness, high melting point, etc. They are a kind of high-temperature material that can be used above 1500 degrees and have great application potential in extreme environments in aerospace and other fields. Among them, carbide ultra-high temperature ceramics, mainly including ZrC, HfC, TaC, TiC, etc., are widely used because of their extremely high melting point, superior mechanical properties, excellent electrical conductivity and high temperature stability. In addition, in recent years, a series of multi-component ceramics such as carbide ceramic binary solid solution, medium entropy carbide ceramics, and high entropy carbide ceramics not only have the characteristics of traditional carbide ceramics, but also their hardness, modulus, and high temperature stability can be adjusted under the action of multiple principal components and have achieved great performance improvement.
[0003] However, carbide ultra-high temperature ceramics have low toughness, which limits their wide application. Nanophase toughening is an effective method to improve the mechanical properties of carbide ceramics. Among them, graphene has excellent mechanical, electrical and thermal properties and is an ideal nano-toughening phase. If graphene and carbide ultra-high temperature ceramics can be evenly dispersed, it is expected to simultaneously improve the thermal conductivity, electrical conductivity and mechanical properties of carbide ultra-high temperature ceramics. However, in existing reports, the mixing of graphene and carbide ceramics is mostly mechanical mixing, and then the composite material is obtained through subsequent preparation processes, which easily leads to uneven dispersion and agglomeration of graphene, which in turn causes limited improvement of graphene, or even the performance of the composite material decreases instead of increases. Secondly, the traditional synthesis method of carbide ceramics has the disadvantages of complex process, long preparation cycle, high energy consumption, and high environmental pollution, and it is difficult to achieve simultaneous preparation or simultaneous compounding with graphene.
[0004] Therefore, it is of great significance to develop a universal method for rapidly preparing carbide ultrahigh temperature ceramic nanoparticle-graphene composite materials, and to prepare composite material powders with the advantages of uniform mixing of graphene and carbide ceramics, large adjustable component space, and high purity. Summary of the invention
[0005] Technical issues to be solved
[0006] In order to avoid the shortcomings of the prior art, the present invention proposes a carbide ultra-high temperature ceramic nanoparticle-graphene composite material and a rapid preparation method and application thereof, using graphene oxide as a carbon source and substrate, metal chloride as a raw material, and adopting the Joule heating method to simultaneously achieve the reduction of graphene oxide and the rapid and uniform synthesis of carbide ultra-high temperature ceramic nanoparticles on graphene through short-term rapid high-temperature thermal shock.
[0007] Technical Solution
[0008] A method for preparing a carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-time rapid high temperature thermal shock, characterized by the following steps:
[0009] Step 1: dispersing graphene oxide powder in deionized water to prepare a graphene oxide aqueous solution with a concentration of 0.1 to 10 mg / mL;
[0010] Step 2: adding metal chloride powder to the graphene oxide aqueous solution to obtain a mixed solution; adding the mixed solution to a vacuum filtration device, placing the filter membrane at room temperature to dry for 12 to 24 hours after filtration, and then peeling off the graphene oxide-metal chloride membrane from the filter membrane;
[0011] Step 3: sandwich the graphene oxide-metal chloride film between two carbon-based heating bodies, place it in a Joule heating device, evacuate it, and then fill it with protective gas. After powering on, adjust the voltage and current. The power-on time is 1 to 30 seconds, and the carbide ultra-high temperature ceramic nanoparticle-graphene composite material is obtained;
[0012] The calcination synthesis time of the preparation process is shortened from several hours to several seconds to tens of seconds, thereby shortening the preparation cycle of the carbide ceramic-graphene composite material, improving the synthesis efficiency, and better saving energy and protecting the environment.
[0013] In the step 1, ultrasound is used for 0.5 to 12 hours during the mixing.
[0014] Weigh 10-200 mg of metal chloride powder and add it to 5-20 mL of graphene oxide aqueous solution.
[0015] The magnetic stirring in step 2 is performed for 5 to 60 minutes to obtain a mixed solution.
[0016] The metal chloride is a combination of one or more of TiCl4, NbCl4, ZrCl4, HfCl4, TaCl5, MoCl5 and VCl3.
[0017] The carbon-based heating body in step 3 is: graphite paper, carbon fiber cloth, carbon nanotube paper, graphite sheet, carbon fiber paper or carbon / carbon composite material.
[0018] The voltage of the Joule heating device in step 3 is 10-80V, and the current is less than 200A.
[0019] The protective gas in step 3 is nitrogen or argon.
[0020] A carbide ultra-high temperature ceramic nanoparticle-graphene composite material prepared by the method according to any one of claims 1 to 8, characterized in that the carbide ultra-high temperature ceramic particles are TiC, NbC, ZrC, HfC, TaC, MoC, Hf x Zr y C. Hf x Ta y C. Ta x Zr y C. Hf x Zr y Ta z C, (Hf-Zr-Ta-Nb)C, (Hf-Zr-Ta-Ti)C or (Hf-Zr-Ta-Nb-Ti)C.
[0021] The carbide ultra-high temperature ceramic particles are evenly distributed in the graphene sheets.
[0022] An application of the method is characterized by being used for large-scale macro-production of carbide ceramic-graphene composite materials.
[0023] Beneficial Effects
[0024] The invention proposes a carbide ultra-high temperature ceramic nanoparticle-graphene composite material and a rapid preparation method and application thereof. The rapid preparation method uses graphene oxide as a carbon source and substrate, metal chloride as a raw material, and adopts a Joule heating method to simultaneously achieve the reduction of graphene oxide and the rapid and uniform synthesis of carbide ultra-high temperature ceramic nanoparticles on graphene through short-term rapid high-temperature thermal shock.
[0025] This scheme uses graphene oxide as the substrate, which has rich functional groups on the surface. It can not only uniformly adsorb sufficient metal chlorides, but also can be used as a carbon source for the synthesis of carbide ultra-high temperature ceramics. During the high-temperature thermal shock process, this scheme not only achieves the reduction of graphene oxide to form a graphene substrate, but also forms carbide ultra-high temperature ceramic nanoparticles in situ on the graphene surface, with uniform particle size, good distribution, no agglomeration, and strong binding force.
[0026] More importantly, the present invention can prepare carbide ultra-high temperature ceramic nanoparticle-graphene composite materials containing any one or more of the elements Hf, Zr, Ti, Ta, Nb, Mo and V, indicating that the present scheme has extremely strong universality, and composite materials of a series of carbide ultra-high temperature ceramics and graphene such as mono-, binary solid solutions, ternary medium entropy, and high entropy (greater than or equal to quaternary) can be quickly prepared in one step, and the ceramic components have a large adjustable space, high purity, and uniform distribution of metal elements.
[0027] In addition, the present invention realizes the simple, efficient, ultra-fast and low-energy synthesis of carbide ceramic-graphene composite materials, shortening the traditional calcination synthesis time of several hours to several seconds to tens of seconds, overcoming the shortcomings of the traditional high-temperature sintering method of long calcination time, time-consuming and energy-consuming, and high cost, greatly shortening the preparation cycle of carbide ceramic-graphene composite materials, improving the synthesis efficiency, and better saving energy and protecting the environment. In addition, the synthesis process of the present invention is simple and controllable, the preparation device is also relatively simple, and the equipment requirements are relatively low, which can reduce the industrial production cost, and is suitable for large-scale and large-scale preparation of carbide ceramic-graphene composite materials, so that it can be more widely used. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0029] Figure 1 : Schematic diagram of the formation process of the carbide ultra-high temperature ceramic nanoparticle-graphene composite material prepared by the present invention;
[0030] Figure 2 : SEM characterization image of the ZrC nanoparticle-graphene composite material prepared by the present invention;
[0031] Figure 3 : XRD spectrum of the ZrC nanoparticle-graphene composite material prepared by the present invention;
[0032] Figure 4 : SEM characterization image of the HfC nanoparticle-graphene composite material prepared by the present invention;
[0033] Figure 5 : XRD pattern of the HfC nanoparticle-graphene composite material prepared by the present invention;
[0034] Figure 6 : TEM characterization image of the HfC nanoparticle-graphene composite material prepared by the present invention;
[0035] Figure 7 : Hf prepared by the present inventionx Zr y Ta z HAADF image and corresponding surface scan energy spectrum of the entropy ceramic nanoparticle-graphene composite material in C. DETAILED DESCRIPTION
[0036] The present invention will now be further described with reference to the embodiments and the accompanying drawings:
[0037] A method for preparing a carbide ultra-high temperature ceramic nanoparticle-graphene composite material, the specific process is as follows:
[0038] 1. Weigh a certain mass of graphene oxide powder, disperse it in deionized water, and ultrasonicate for 0.5 to 12 hours to obtain a graphene oxide aqueous solution with a concentration of 0.1 to 10 mg / mL.
[0039] 2. Weigh 10-200 mg of metal chloride powder and add it to 5-20 mL of graphene oxide aqueous solution, and stir magnetically for 5-60 min to obtain a mixed solution; add the mixed solution to a vacuum filtration device, and after filtration, place the filter membrane at room temperature to dry for 12-24 h, and then peel off the graphene oxide-metal chloride membrane from the filter membrane.
[0040] 3. The graphene oxide-metal chloride film obtained in step 2 is sandwiched between two carbon-based heating bodies, placed in a Joule heating device, evacuated, and then filled with protective gas. After power is turned on, the voltage and current are adjusted, and the power-on time is 1 to 30 seconds to obtain a carbide ultra-high temperature ceramic nanoparticle-graphene composite material.
[0041] Preferably, the metal chloride described in step 2 is a combination of one or more of, but not limited to, TiCl4, NbCl4, ZrCl4, HfCl4, TaCl5, MoCl5, and VCl3.
[0042] Preferably, the carbon-based heating body described in step three is one of but not limited to: graphite paper, carbon fiber cloth, carbon nanotube paper, graphite sheet, carbon fiber paper, carbon / carbon composite material, etc., with a size of 40-100 mm in length and 10-30 mm in width.
[0043] Preferably, the voltage of the Joule heating device described in step three is 10-80V, and the current is less than 200A.
[0044] Preferably, the protective gas in step three is nitrogen or argon.
[0045] Preferably, the carbide ultra-high temperature ceramic particles in step 3 are one of but not limited to TiC, NbC, ZrC, HfC, TaC, MoC, Hf x Zr y C. Hfx Ta y C. Ta x Zr y C. Hf x Zr y Ta z C, (Hf-Zr-Ta-Nb)C, (Hf-Zr-Ta-Ti)C, (Hf-Zr-Ta-Nb-Ti)C.
[0046] Embodiment 1:
[0047] 1. Weigh a certain mass of graphene oxide powder, disperse it in deionized water, and ultrasonicate for 0.5 h to obtain a graphene oxide aqueous solution with a concentration of 0.1 mg / mL.
[0048] 2. Weigh 10 mg of ZrCl4 powder and add it to 5 mL of graphene oxide aqueous solution, stir magnetically for 5 minutes to obtain a mixed solution; add the above mixed solution to a vacuum filtration device, place the filter membrane at room temperature to dry for 12 hours after filtration, and then peel off the graphene oxide-ZrCl4 membrane from the filter membrane.
[0049] 3. The graphene oxide-ZrCl4 film obtained in step 2 is sandwiched between two 30mm×40mm graphite paper heating bodies, placed in a Joule heating device, evacuated, and then filled with nitrogen protective gas. After power-on, the voltage is adjusted to 50V and the power-on time is 2s to obtain a ZrC nanoparticle-graphene composite material.
[0050] Embodiment 2:
[0051] 1. Weigh a certain mass of graphene oxide powder, disperse it in deionized water, and ultrasonicate for 3 h to obtain a graphene oxide aqueous solution with a concentration of 2 mg / mL.
[0052] 2. Weigh 50 mg of HfCl4 powder and add it to 20 mL of graphene oxide aqueous solution, stir magnetically for 20 minutes to obtain a mixed solution; add the above mixed solution to a vacuum filtration device, place the filter membrane at room temperature to dry for 12 hours after filtration, and then peel off the graphene oxide-HfCl4 membrane from the filter membrane.
[0053] 3. The graphene oxide-HfCl4 film obtained in step 2 is sandwiched between two 30mm×60mm carbon cloth heating bodies, placed in a Joule heating device, evacuated, and then filled with argon protective gas. After power-on, the voltage is adjusted to 30V and the power-on time is 5s to obtain the HfC nanoparticle-graphene composite material.
[0054] Embodiment 3:
[0055] 1. Weigh a certain mass of graphene oxide powder, disperse it in deionized water, and ultrasonicate for 6 hours to obtain a graphene oxide aqueous solution with a concentration of 4 mg / mL.
[0056] 2. Weigh 100 mg of HfCl4 and TaCl5 powder (mass ratio is 1:1) and add them to 10 mL of graphene oxide aqueous solution, stir magnetically for 30 minutes to obtain a mixed solution; add the above mixed solution to a vacuum filtration device, place the filter membrane at room temperature to dry for 24 hours after filtration, and then peel off the graphene oxide-HfCl4-TaCl5 membrane from the filter membrane.
[0057] 3. The graphene oxide-HfCl4-TaCl5 film obtained in step 2 was sandwiched between two 25mm×80mm carbon / carbon composite material heating bodies, placed in a Joule heating device, evacuated, and then filled with nitrogen protective gas. After powering on, the voltage was adjusted to 50V and the power-on time was 10s to obtain Hf x Ta y C binary solid solution ceramic nanoparticle-graphene composites.
[0058] Embodiment 4:
[0059] 1. Weigh a certain mass of graphene oxide powder, disperse it in deionized water, and ultrasonicate for 12 h to obtain a graphene oxide aqueous solution with a concentration of 5 mg / mL.
[0060] 2. Weigh 150 mg of ZrCl4, HfCl4 and TaCl5 powder (mass ratio of 1:1:1) and add them to 15 mL of graphene oxide aqueous solution, stir magnetically for 40 minutes to obtain a mixed solution; add the above mixed solution to a vacuum filtration device, place the filter membrane at room temperature to dry for 24 hours after filtration, and then peel off the graphene oxide-ZrCl4-HfCl4-TaCl5 membrane from the filter membrane.
[0061] 3. The graphene oxide-ZrCl4-HfCl4-TaCl5 film obtained in step 2 was sandwiched between two 20mm×80mm carbon fiber cloth heating bodies, placed in a Joule heating device, evacuated, and then filled with argon protective gas. After powering on, the voltage was adjusted to 60V and the power-on time was 20s to obtain Hf x Zr y Ta z C medium entropy ceramic nanoparticle-graphene composites.
[0062] Embodiment 5:
[0063] 1. Weigh a certain mass of graphene oxide powder, disperse it in deionized water, and ultrasonicate for 12 hours to obtain a graphene oxide aqueous solution with a concentration of 10 mg / mL.
[0064] 2. Weigh 200 mg of TiCl4, ZrCl4, HfCl4 and TaCl5 powder (mass ratio of 1:1:1:1) and add them to 20 mL of graphene oxide aqueous solution, stir magnetically for 60 minutes to obtain a mixed solution; add the above mixed solution to a vacuum filtration device, place the filter membrane at room temperature to dry for 24 hours after filtration, and then peel off the graphene oxide-TiCl4-ZrCl4-HfCl4-TaCl5 membrane from the filter membrane.
[0065] 3. The graphene oxide-TiCl4-ZrCl4-HfCl4-TaCl5 film obtained in step 2 is sandwiched between two 20mm×100mm graphite paper heating bodies, placed in a Joule heating device, evacuated, and then filled with protective gas. After power-on, the voltage is adjusted to 80V and the power-on time is 30s to obtain the (Hf-Zr-Ta-Ti)C high-entropy ceramic nanoparticle-graphene composite material.
[0066] Figure 1 This is a schematic diagram of the preparation process of the carbide ultra-high temperature ceramic nanoparticle-graphene composite material proposed in the present invention. During the preparation process, graphene oxide powder and metal chloride powder are evenly mixed. The former is a carbon source and a substrate, and the latter is a raw material. The two are made into a thin film and sandwiched between two carbonaceous heating bodies. The film is placed in a Joule heating device and powered on for heating. An inert protective gas is introduced throughout the process. Under high-temperature thermal shock, the carbide ultra-high temperature ceramic nanoparticle-graphene composite material can be obtained in just a few seconds.
[0067] Figure 2 This is a SEM characterization image of the ZrC nanoparticle-graphene composite material prepared by the present invention; a large number of ZrC particles are evenly distributed in the graphene sheet layer, and the diameter thereof is between 200nm and 800nm.
[0068] Figure 3 From the XRD spectrum of the ZrC nanoparticle-graphene composite material prepared in the present invention, diffraction peaks of ZrC (111), (200), (220), (311) and (222) can be observed, indicating the successful synthesis of ZrC.
[0069] Figure 4 This is a SEM characterization image of the HfC nanoparticle-graphene composite material prepared by the present invention. A large number of HfC particles are evenly distributed in the graphene substrate, and their diameters are between 0.4 and 2 μm.
[0070] Figure 5 From the XRD spectrum of the HfC nanoparticle-graphene composite material prepared in the present invention, diffraction peaks of HfC (111), (200), (220), (311), (222) and (400) can be observed, indicating that HfC is successfully synthesized.
[0071] Figure 6 This is a TEM characterization image of the HfC nanoparticle-graphene composite material prepared in the present invention, and a large number of synthesized HfC particles can be clearly observed, and the diameters thereof are between 50 nm and 300 nm.
[0072] Figure 7 The Hf prepared by the present invention x Zr y Ta z C shows the HAADF image and corresponding surface scan energy spectrum of the high-entropy ceramic nanoparticle-graphene composite material. It can be seen from the figure that the three elements Hf, Zr and Ta are evenly distributed inside the entire nanoparticle.
[0073] The technical solution of the present invention is not limited to the specific implementation methods listed above, and various changes can be made. That is, all other embodiments obtained according to the claims and description of the present invention application belong to the protection scope of the present invention.
Claims
1. A method for preparing a carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-term rapid high temperature thermal shock, characterized in that Here are the steps: Step 1: dispersing graphene oxide powder in deionized water to prepare a graphene oxide aqueous solution with a concentration of 0.1 to 10 mg / mL; Step 2: adding metal chloride powder to the graphene oxide aqueous solution to obtain a mixed solution; adding the mixed solution to a vacuum filtration device, placing the filter membrane at room temperature to dry for 12 to 24 hours after filtration, and then peeling off the graphene oxide-metal chloride membrane from the filter membrane; Step 3: sandwich the graphene oxide-metal chloride film between two carbon-based heating bodies, place it in a Joule heating device, evacuate it, and then fill it with protective gas. After powering on, adjust the voltage and current. The power-on time is 1 to 30 seconds, and the carbide ultra-high temperature ceramic nanoparticle-graphene composite material is obtained; The calcination synthesis time of the preparation process is shortened from several hours to several seconds to tens of seconds, thereby shortening the preparation cycle of the carbide ceramic-graphene composite material, improving the synthesis efficiency, and better saving energy and protecting the environment.
2. The method for preparing carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-time rapid high temperature thermal shock according to claim 1, characterized in that: In the step 1, ultrasound is used for 0.5 to 12 hours during the mixing.
3. The method for preparing carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-time rapid high temperature thermal shock according to claim 1, characterized in that: Weigh 10-200 mg of metal chloride powder and add it to 5-20 mL of graphene oxide aqueous solution.
4. The method for preparing carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-time rapid high temperature thermal shock according to claim 1, characterized in that: In step 2, magnetic stirring is performed for 5 to 60 minutes to obtain a mixed solution.
5. The method for preparing carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-time rapid high temperature thermal shock according to claim 1, characterized in that: The metal chloride is a combination of one or more of TiCl4, NbCl4, ZrCl4, HfCl4, TaCl5, MoCl5 and VCl3.
6. The method for preparing carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-time rapid high temperature thermal shock according to claim 1, characterized in that: The carbon-based heating body in step 3 is: graphite paper, carbon fiber cloth, carbon nanotube paper, graphite sheet, carbon fiber paper or carbon / carbon composite material.
7. The method for preparing carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-term rapid high temperature thermal shock according to claim 1, characterized in that: The voltage of the Joule heating device in step 3 is 10-80V, and the current is less than 200A.
8. The method for preparing carbide ultra-high temperature ceramic nanoparticle-graphene composite material by short-time rapid high temperature thermal shock according to claim 1, characterized in that: The protective gas in step 3 is nitrogen or argon.
9. A carbide ultra-high temperature ceramic nanoparticle-graphene composite material prepared by the method according to any one of claims 1 to 8, characterized in that The carbide ultra-high temperature ceramic particles are TiC, NbC, ZrC, HfC, TaC, MoC, Hf x Zr y C. Hf x Ta y C. Ta x Zr y C. Hf x Zr y Ta z C, (Hf-Zr-Ta-Nb)C, (Hf-Zr-Ta-Ti)C or (Hf-Zr-Ta-Nb-Ti)C; the carbide ultrahigh temperature ceramic particles are uniformly distributed in the graphene sheet.
10. An application of the method according to any one of claims 1 to 8, characterized in that: Used for large-scale preparation of carbide ceramic-graphene composites.
Citation Information
Patent Citations
Preparation method and application of nitrogen doped molybdenum carbide / graphene composite
CN109256545A
Smelting method and patterning method of nano metal particles
CN109877341A
Method of preparing porous carbon loaded metal or metal carbide nanoparticles quickly
CN110695366A
Silicon carbide / graphene bionic composite material for bulletproof armor and preparation method thereof
CN111825459A
Device and method for continuously synthesizing powder material based on thermal impact
CN112404449A